Effect of Fe-Doping on the Properties of CdO Thin Films Prepared by Pulsed Laser Deposition - Abbass, Haidar K.; Khidir, Ali H. (Iraqi Journal of Science, 2022)
Pure and iron-doped cadmium oxide ((CdO)1-xFex) thin films at different ratios were prepared using  pulsed laser deposition technique. The X-ray diffraction showed a polycrystalline structure for all samples associated with cubic CdO structure. Another phase appeared at the highest ratio corresponding to the cubic Fe phase. Crystallinity was enhanced and crystalline size increased with increasing Fe ratio. AFM measurements showed that increase of  Fe ratio led to an increase in the average particle diameter. In addition, the distribution of particle size became wide and of irregular behaviour, as well as increasing of the average roughness and the root-mean-square roughness. Increasing the Fe ratio caused the band gap to decrease from 2.3 eV to 2.1 eV. Hall effect measurements showed that the charge carrier concentration increased from 7.6 to 12.4 cm-3 with the increase of Fe ratio, while the mobility had the opposite behaviour, it decreased from 0.3 to 0.13 cm2/V.s as Fe content increased from 0 to 0.5 atom ratio.